The Influence of Profitability, Leverage and Sales Growth on Avoidance Tax - Wahyu Anggraini; Abdul Rahmat (International Journal of Economics and Management Sciences, 2024)
This study aims to determine the influence of profitability, leverage and sales growth on tax avoidance. This research sample will be obtained from Property and Real Estate Sector Companies listed on the Indonesia Stock Exchange in the 2021-2022 period. To find out the relationship between variables, data analysis is carried out. The analysis used in this study is multiple regression analysis where for partial testing using statistical test t and simultaneous testing using the anova statistical test and before this test is carried out first a classical assumption test. This research is classified as TKT 3, which is proof of concept of functions and/or important characteristics analytically and experimentally.